The Socio-Psychological Dimension in Enhancing Employee Performance at the Ministry of Religious Affairs Office - Jamaluddin; Rif'at Al-Razi, Muhammad (Fakultas Psikologi, Universitas Islam Negeri (UIN) Sunan Gunung Djati Bandung, 2025)
This research is based on the performance of human resources, which is determined by the urgency of strengthening the capacity of human resources officials at the Office of the Ministry of Religion, Cimahi City, West Java. Efforts to develop the capacity of human resources or apparatus are focused on the availability of professional personnel who have technical abilities or competencies, which can be carried out through various activities and efforts to improve the performance of apparatus by optimizing dimensions related to strengthening the capacity of human resources in question. This research aims to determine the process of increasing the competency of human resources or apparatus within the Office of the Ministry of Religion of Cimahi City as well as other aspects that influence strengthening the capacity of human resources within the Office of the Ministry of Religion of Cimahi City. This research uses a qualitative approach with descriptive analysis methods. The theory used is Grindle's (1980) theory of strengthening or developing HR capacity, including education and training, salary systems, working conditions, and human resource recruitment. The research results showed that strengthening the capacity of performance-based human resources at the Cimahi City Ministry of Religion Office had been carried out so that it had an impact on improving the performance of human resources in accordance with their main tasks and functions. Working conditions are relatively good, as seen from regular coaching between superiors and staff. The payroll system is in accordance with applicable regulatory procedures; human resource recruitment has gone through specified procedures but has not yet produced personnel with optimal capacity. Meanwhile, supporting factors, including adequate normative regulatory support, employee motivation, and cooperation between human resources, are quite good. Meanwhile, inhibiting factors include budget shortages, the absence of post-training evaluation, and synergy between human resources that is not yet optimal.